Treatment of acute promyelocytic leukemia with arsenic trioxide: clinical results and open questions. Issue 9 (September 2013) - Lengfelder, Eva; Hofmann, Wolf-Karsten; Nowak, Daniel
Acute promyelocytic leukemia (APL) is a rare form of acute myeloid leukemia. The specific translocation t(15;17), which results in the fusion gene PML–RARA is the diagnostic and pathomechanistic hallmark of APL. By combination, treatment consisting of the differentiating agent all- trans retinoic acid (ATRA), which targets this molecular lesion, and cytotoxic chemotherapy, cure can be achieved in over 70% of patients. Recently, arsenic trioxide (ATO) has emerged to be the most active single agent in the treatment of APL. Previous studies employing ATO in relapse settings reported average complete remission rates of 85% and a mean overall survival of over 60%. In recent approaches installing ATO in first-line treatment, ATO-induced response rates comparable to previous combination regimen. The results of these newer studies indicate that the backbone of chemotherapy can be dramatically reduced or completely replaced by ATO and ATRA with similar or even better outcome.